The Book of Concord and Human Sexuality, Seen Through the Institution of Marriage - Wengert, Timothy J. (Dialog, 2009)
Although The Book of Concord says only a few things about sexuality explicitly, by observing the distinction between law and gospel and the way the reformers correlate the law with their social situation, today's Lutheran readers may reach broader conclusions about their approach to such matters. The most important issue regarding sexuality in the sixteenth century arose from the reformers' desire to distinguish monastic celibacy from true chastity and thus to support their conviction that every-day married life was a God-pleasing, Christian vocation.